A framework for playful pedagogy: Nurturing child imagination in second language learning - Bao, Dat; Nguyen, Tran Thi Hoang (Universitas Ahmad Dahlan, 2025)
This conceptual article argues that although imagination is a highly important dynamic of the mind with strong potential to assist language development, imagination alone does not work by itself. Instead, a strategic framework is needed to support imagination by connecting it with playful teaching and amusing content. The article begins by pinpointing what playful pedagogy means and what role imagination plays in the learning process. Secondly, the discussion presents some challenges to such learning, delving particularly into some constraints on child imagination and other constraints on English learning among children. Thirdly, the discussion highlights the need for a playful pedagogy and amusing content to support it. This is followed by some insights into nurturing imagination for learning. Finally, the article unpacks the above-mentioned framework in ways that would assist task design in language education.